Unleashing the Power of AI: Revolutionizing Plastic Waste Management for Sustainable Development in Developing Nations - Solaja, Oludele Mayowa (Diponegoro University, 2024)
Plastic waste pollution poses a significant environmental challenge worldwide, particularly in developing countries like Nigeria, where limited waste management infrastructure exacerbates the problem. This paper examines the potential of artificial intelligence (AI) technologies to address plastic waste reduction in developing countries, with a focus on the Nigerian context. Through a comprehensive analysis of challenges, opportunities, case studies, policy implications, and recommendations, the paper highlights the transformative role of AI in waste management. Challenges such as infrastructure gaps, data scarcity, and ethical considerations are identified, alongside opportunities for innovation, efficiency, and sustainability. Case studies from developed and developing countries illustrate successful AI applications in waste collection, sorting, recycling, and pollution monitoring. Policy implications emphasize the importance of comprehensive legislation, investment in infrastructure and technology, public awareness, and cross-sectoral collaboration. Recommendations include extended producer responsibility policies, landfill bans, education campaigns, and international cooperation. The future of AI-driven plastic waste reduction in developing countries hinges on technological advancement, collaborative partnerships, increased investment, supportive policies, and regulatory frameworks. By harnessing the power of AI technologies and collective action, developing countries can address the plastic waste crisis, promote environmental sustainability, and foster a cleaner, greener future for all.